Answer:
See the explanations below
Step-by-step explanation:
Given the function y = x²+12x
We are to find the inverse and identify the error in the calculation:
Step 1: Replace y with x
x = y²+12y
First Error: There is an error here y, the variable attached to x should be y and not x that is y = y²+12y and not y = y²+12x. The x should be totally replaced with
The second error is where he wrote y = √-11x
The square root of a value must return both negative and positive value not only the positive value. Hence the correct expression should have been y = ±√-11x (Note that the sign ± was introduced)
Third error: Since the value inside the square rot is a negative value hence the value of x must be negative i.e x must be less than zero not greater then. The correct inequality expression should have been x <0 and not
x< 0